WHO mental health gap action programme (mhGAP) intervention guide: updated systematic review on evidence and impact. Issue 3 (26th April 2021) - Keynejad, Roxanne; Spagnolo, Jessica; Thornicroft, Graham
Abstract : Question: There is a large worldwide gap between the service need and provision for mental, neurological and substance use disorders. WHO's Mental Health Gap Action Programme (mhGAP) intervention guide (IG), provides evidence-based guidance and tools for assessment and integrated management of priority disorders. Our 2017 systematic review identified 33 peer-reviewed studies describing mhGAP-IG implementation in low-income and middle-income countries. Study selection and analysis: We searched MEDLINE, Embase, PsycINFO, Web of Knowledge, Scopus, CINAHL, LILACS, ScieELO, Cochrane, PubMed databases, 3ie, Google Scholar and citations of our review, on 24 November 2020. We sought evidence, experience and evaluations of the mhGAP-IG, app or mhGAP Humanitarian IG, from any country, in any language. We extracted data from included papers, but heterogeneity prevented meta-analysis. Findings: Of 2621 results, 162 new papers reported applications of the mhGAP-IG. They described mhGAP training courses (59 references), clinical applications (n=49), research uses (n=27), contextual adaptations (n=13), economic studies (n=7) and other educational applications (n=7). Most were conducted in the African region (40%) and South-East Asia (25%). Studies demonstrated improved knowledge, attitudes and confidence post-training and improved symptoms and engagement with care, post-implementation. Research studies compared mhGAP-IG-enhanced usual care with task-shared psychological interventions and adaptation studies optimised mhGAP-IG implementation for different contexts. Economic studies calculated human resource requirements of scaling up mhGAP-IG implementation and other educational studies explored its potential for repurposing. Conclusions: The diverse, expanding global mhGAP-IG literature demonstrates substantial impact on training, patient care, research and practice. Priorities for future research should be less-studied regions, severe mental illness and contextual adaptation of brief psychological interventions.